К вопросу о первичном ареале Artemisia dracunculus L. - Бойко, А.В. (Промышленная ботаника, 2010)
Обсуждается флорогенезисный статус Artemisia dracunculus L. на территории Северной Америки, Западной Европы и Украины. В результате анализа имеющихся материалов расширены границы первичного ареала вида на территории Украины. The floragenesis status of Artemisia dracunculus L. on the territory of North America, Western Europe and Ukraine has been discussed. The analysis of available materials has shown that the borders of the primary natural habitat on the territory of Ukraine has been extended.